Pemetaan Potensi Muskuloskletal Disorders (MSDs) pada Aktivitas Manual Material Handling (MMH) Kelapa Sawit - Roberta Zulfhi Surya (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Palm oil (Elaeis) is an important industrial plants producing cooking oil, industrial oil, and fuel (biodiesel) as the palm oil business is currently exceptional. Work activities in palm oil plantations, especially, loading and unloading are potentially causing Musculoskletal Disorders (MSDs). Manual Materials Handling (MMH) activities in palm oil business potentially occurs MSDs at (1) the upper neck; (2) the lower neck; (3) the left shoulder; (4) the right shoulder; (5) the backs; (6) on the right arm; (7) under the left arm; (8) the right forearm; (9) the left wrist; (10) the right wrist; (11) the left hand; and (12) the right hand. MSDs happens due to these 12 body parts are in direct contact with the activities. The primary cause of MSDs is unnatural working attitude and excessive muscle tension began from the design of a working system that is designed not in accordance with the workers’ limitations.Keywords: Palm Oil, Musculoskletal Disorders, Manual Material Handling